2022
DOI: 10.1155/2022/4688356
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Prognosis of Ultrasound-Guided Percutaneous Catheter Drainage in Patients with Liver Abscess Complicated with Septic Shock

Abstract: Objective. Currently, the therapeutic effect and outcomes of US-PCD in patients with liver abscess and septic shock remain unclear. This study is aimed at investigating the effects of ultrasound-guided percutaneous catheter drainage (US-PCD) on the prognosis of patients with liver abscess complicated with septic shock. Method. We retrieved and assessed the data of 120 patients with liver abscess complicated with septic shock diagnosed at our hospital from January 2019 to March 2021. The patients underwent US-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%